Students' Perception In Bruno Mars' Song "Versace On The Floor” - Inayahtullah R Peder; Santi Prastyowati (Jurnal Perempuan dan Anak, 2020)
Song is a set of phrases that is accompanied by musical rhythms, contain message in the lyrics and can be sung. These days, there are many popular songs that have negative value for listeners. Conveying message about sex, love or portrayal of women is still a social debate because of cultural differences as well as rules in the environment. “Versace on the Floor” was one of the Bruno Mars’ famous song which contain sexual message in its lyrics. In this case, this study aims at discovering of students’ perception on Bruno Mars song “Versace on the Floor” about different gender regarding language used fin the song and allegedly contain elements of sex. This study used qualitative research methods to provide a detailed perspective of people about social phenomena such as culture or song. The researcher used students of University Muhammadiyah Malang as research subjects. The number of participants consisted of 20 female students and 20 male students. This research used questionnaire, interview guideline and document analysis to get data. The result indicated that most of students agreed that Bruno Mars’ song “Versace on the Floor” conveys sexual message. Both female and male students agreed that the song conveyed sexual message (female scored the greater number). However, several students thought that “Versace on the Floor” did not imply sexual message. They thought that it was a romantic song, which was expressed like having sexual message. Moreover, more than a half of the respondents (female scored greater number) thought that “Versace on the Floor” had a good melody. Moreover, the song should not be banned in Indonesia because the song was only heard as entertainment.